Ozone profile measurements at McMurdo Station Antarctica during the spring of 1987 - Hofmann, D. J.; Rosen, J. M.; Carpenter, J. R.; Hereford, J.; Harder, J. W. (1988)
During the Antarctic spring of 1986, 33 ozone soundings were conducted from McMurdo Station. These data indicated that the springtime decrease in ozone occurred rapidly between the altitudes of 12 and 20 km. During 1987, these measurements were repeated with 50 soundings between 29 August and 9 November. Digital conversions of standard electrochemical cell ozonesondes were again employed. The ozonesonde pumps were individually calibrated for flow rate as the high altitude performance of these pumps have been in question. While these uncertainties are not large in the region of the ozone hole, they are significant at high altitude and apparently resulted in an underestimate of total ozone of about 7 percent (average) as compared to the Total Ozone Mapping Spectrometer (TOMS) in 1986, when the flow rate recommended by the manufacturer was used. At the upper altitudes (approx. 30 km) the flow rate may be overestimated by as much as 15 percent using recommended values (see Harder et al., The UW Digital Ozonesonde: Characteristics and Flow Rate Calibration, poster paper, this workshop). These upper level values are used in the extrapolation, at constant mixing ratio, required to complete the sounding for total ozone. The first sounding was on 29 August, prior to major ozone depletion, when 274 DU total ozone (25 DU extrapolated) was observed. By early October total ozone had decreased to the 150 DU range; it then increased during mid-October owing to motion of the vortex and returned to a value of 148 DU (29 DU extrapolated) on 27 October.